Chinese herbal medicine packet therapy for a case of contrast agent extravasation in enhanced CT scanning and related nursing experience (CT增强扫描造影剂外渗1例的中药封包治疗及护理体会) - ZHAO Yan (赵燕); LIU Shuhong (刘书红); ZHAO Yanan (赵亚楠); HUO Jingjing (霍晶晶) (Journal of International Translational Medicine Limited, 2021)
This paper summarized the Chinese herbal medicine packet therapy for a case of contrast agent extravasation in enhanced CT scanning and related nursing experience. On the basis of routine care (external application of 50% magnesium sulfate), A Traditional Chinese Medicine nursing technique-Chinese herbal medicine packet therapy-was carried out to reduce the pain and improve the swelling relief after contrast agent extravasation. (本文总结1例肿瘤患者CT增强扫描中造影剂外渗的护理体会。在常规护理(50%硫酸镁湿敷)的基础上, 采用中医特色护理技术中药封包疗法进行干预, 促进局部组织快速消肿, 有效减轻患者痛苦。)